PENGARUH MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN UNIVERSITAS ANDALAS DALAM RANGKA MENERAPKAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM (BLU) - Siska, Adilla Juita (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2014)
This study aims to obtain empirical evidence of the influence of work motivation on employee job satisfaction Andalas University in order to implement financial management Public Service Agency (BLU). To perform the testing stages of data used 284 employees at the University of Andalas Padang. The process of data collection is done by using the observation that involves researchers directly. The data used is primary data which sought to disseminate research questionnaires to the respondents who have met the sampling criteria. In this study there are two types of variables are used, the first is the independent variable is motivation. The second is the dependent variable is job satisfaction. The process of hypothesis testing is done with quantitative methods. The model used is a simple linear regression. Based on the test results found that motivation significantly influence employee job satisfaction Andalas University in order to implement financial management Public Service Agency (BLU)